Investment Strategy of Financial Intermediaries on the Financial Market of the Republic of Srpska in the Conditions of Globalization - Starčević, Vitomir; Milošević, Srđan (International Scientific Conference Strategic Management and Decision Support Systems in Strategic Management, 2021)
In the current conditions of global processes, in addition to determined ideological commitment to the development of a market economy in the Republic of Srpska, the capacity building of financial institutions for decisive action in new market conditions has been actively approached. In this sense, an important role is given to financial intermediaries, both deposit and non-deposit. These are financial institutions that have large capital and actively participate in the financial market. Therefore, financial intermediaries result in raising the efficiency of the financial system and have significant positive effects on the development of the economy. Therefore, the research in this paper is focused on showing the importance of financial intermediaries in the financial market of Republika Srpska under the influence of globalization. In this regard, the aim of the research is focused on showing the profitability of the strategy of investing free funds by financial intermediaries in the financial market of Republika Srpska. In connection with the goal of the research, the importance in the research is given to the structure of investments of financial intermediaries on the financial market of the Republic of Srpska in the conditions of globalization.